Validity And Reliability of Field and Wingate Tests to Measure the Anaerobic Power of The Upper Limb Muscles - Alkazaly, Ahmed; Altay, Usama (Journal of Physical Education, 2023)
The research aimed to find the validity and reliability of physical tests (forward medicine ball throwing from a sitting, push-up, bench press) and Wingate anaerobic test to measure anaerobic power for upper limb muscles. The researchers used the descriptive approach. The subject was (25) students from the College of Physical Education and Sport Sciences - University of Baghdad. The mean and standard deviation of height, weight, and age were (175.63 ± 4.83 cm) (65.94 ± 1.64 kg) (22.81 ± 1.64 years), respectively. The four tests were implemented twice, with a time interval between one test and another four days. discriminative validity (peripheral comparison) was used to find validity, and interclass correlation - ICC coefficient for reliability. The results showed the validity and reliability of all tests. the results were significant between the upper and lower categories (p < 0.05), and the (ICC) for the four tests was (0.959) (0.828) (0.815) (0.841), respectively.